(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
This article represents an overview of the development of psychological thought concerning the origin of facial expression of emotions. Is facial expression innate or learned? The idea of universality of facial expression seems to be supported by empiricalfindings drawn from studies of the processes underpinning the inception (origination) offacial expression. A comparative account of specificity offacial expression across cultural boundaries is also presented. A section of the paper is devoted to examine the interaction of biological and cultural influence on facial expression. The paper concludes that both evolutionists and cultural relativists failed to give completely satisfactory answers to the fundamental question whether facial expressions are innate or learned.